Detection Of Some Immunological And Biochemical Markers In Seborrheic Dermatitis Patients (Journal of Pharmaceutical Negative Results, 2022)
Background: Seborrheic dermatitis (SD) is a common skin disease in Iraq, which is due to various causes, the most important of whichare fungal infections. The current study aims to isolate Malassezia spp., which may be a risk factor for SD, with the evaluation of somecellular parts of those yeasts, such as GM and BDG, that may play a role in the severity of this disease or its development, as well asevaluating the role of some immunological indicators, such as IL-17A, IL-8, IL-1alpha, histamine, and Cathepsin.Methods: The current study included the collection of 50 samples from patients with SD, the Malassezia species were diagnosedlaboratory by microscopic examination, culture media and biochemical tests. BDG and GM were determined by Fungitell assay whilehistamine, cathepsin S, IL-17A, IL-8, and Il-1alpha were determined by ELISA.Results: Our results showed that most of the patients were female (68%), and they were within the age group of 16-30 years. We alsofound that the highest rates of infection were 34%, 22% and 20% due to the Malassezia globosa, Malassezia sympodialis and Malasseziafurfur. Moreover, we determined an increase serum level of IL-8, IL-17A and IL-1alpha in patients (78.31,789.22 and 97.42 pg/ml,respectively) compared with healthy control group (0.823, 1.09 and 5.41 pg/ml, respectively) and we also found statistical differencesas a result of an increase in some biochemical compounds in patients represented by histamine and cathepsin S (156 and 1190 ng/ml,respectively) and we also found an increase level for fungal compounds such as BDG and GM in SD patients where their average was500 and 4.91 pg/ml, respectively.In conclusion: Malassezia globosa is one of the most important causes of SD, so BDG, GM, histamine, cathepsin S, IL-17A, IL-8, andIL-1alpha indicators can be relied for diagnosis and response to treatment of SD.